Effect of prior anti-tuberculosis treatment on assisted reproductive outcomes in infertile women: a retrospective cohort study - Rong Li; Chen Zhang; Lin Zeng; Yongchang Sun; Xiaoyan Gai; Hongbin Chi; Zikang Sheng; Lixue Chen (BMJ Open)
Purpose Tuberculosis (TB) is a significant factor contributing to infertility. For some infertile patients, chest radiography (CXR) screenings prior to assisted reproductive treatment (ART) reveal old/inactive TB lesions. However, the pregnancy outcomes after ART for such patients who had a history of prior anti-TB treatment remain unclear.Design Retrospective cohort study.Setting Peking University Third Hospital, a tertiary care centre.Participants This study analysed and focused on infertile patients aged 20–50 years with prior TB lesions on CXR (treated/untreated) and normal CXR. Active TB cases were excluded from this study. Patients were categorised into three groups based on CXR findings and prior anti-TB treatment: treated prior-pulmonary TB (PTB) group, untreated prior-PTB group and a non-PTB control group with normal CXR.Primary and secondary outcome measures ART outcomes, including clinical pregnancy rate, miscarriage rate and live birth rate, were compared among the groups.Findings to date Among 8769 patients analysed, including treated prior-PTB group (n=171), untreated prior-PTB group (n=791) and non-PTB group (n=7807). The treated prior-PTB group showed a similar clinical pregnancy rate (41.5% vs 38.1%, p=0.360) and live birth rate (35.3% vs 30.6%, p=0.187) compared with the non-PTB group. The miscarriage rate was slightly lower in the treated prior-PTB group than in the non-PTB group (11.3% vs 15.5%, p=0.325), although the discrepancy was not statistically significant. Compared with the untreated prior-PTB group, the treated prior-PTB group exhibited significantly higher live birth rate (35.3% vs 23.8%, p<0.05), clinical pregnancy rate (41.5% vs 31.7%, p<0.05) and with a lower miscarriage rate (11.3% vs 19.1%, p=0.123), although the latter was not statistically significant. Multivariable regression confirmed significantly higher live birth rates in the treated prior-PTB group versus untreated prior-PTB group (aOR: 1.69, 95% CI: 1.01 to 2.83, p=0.045).Conclusions and Future plans Anti-TB treatment in infertile women with prior PTB lesions was associated with improved ART outcomes, comparable to those in patients without TB lesions. This suggests a potential clinical benefit of anti-TB treatment in improving reproductive outcomes in this population. Further research is warranted to explore ART outcomes in patients with untreated prior TB lesions.